The demand for social insurance: Does culture matter? - Beatrix Brügger; Rafael Lalive; Andreas Steinhauer; Josef Zweimüller (University of Zurich, Department of Economics, 2011)
Can different social groups develop different demands for social insurance of risks to health and work? We study this issue across language groups in Switzerland. Language defines social groups and Swiss language groups are separated by a clear geographic border. Actual levels of social insurance are identical on either side of the within state segments of the language border. We can therefore study the role of culture in shaping the demand for social insurance. Specifically, we contrast at the language border actual voting decisions on country-wide changes to social insurance programs. Key results indicate substantially higher support for expansions of social insurance among residents of Latin-speaking (i.e. French, Italian, or Romansh) border municipalities compared to their German-speaking neighbors in adjacent municipalities. We consider three possible explanations for this finding: informal insurance, ideology, and the media. We find that informal insurance does not vary enough to explain stark differences in social insurance. However, differences in ideology and segmented media markets are potentially important explanatory factors.
Keywords: J21; J64; Z10; 330; culture; language; preferences for social insurance; spatial regression discontinuity; Soziale Gruppe; Sprache; Soziale Sicherung; Nachfrage; Regionale Disparität; Schweiz